Application of Appropriate Technology, Good manufacturing Practice (GMP), Sanitation Standard Operating Procedures (SSOP) in Developing Innovative Regional Superior Products (PPUD) from Processed Coconut Fruit and Nuts - Sudiarta, I Wayan; A. A. Made Semariyani; Singapurwa, Ni Made Ayu Suardani; Ni Made Darmadi (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
The Regional Leading Product Development Program in Carangsari Village, Petang District, Badung Regency, Bali was carried out at the Sari Nadhi Business Study Group. Processing of agricultural products, especially coconut into coconut oil, has been produced and marketed by partners, but not intensively, and partners want to have new superior products by processing local agricultural products, especially coconut and nuts to support Carangsari Tourism Village. Partners do not know the field of business management, so they experience obstacles in managing production and marketing. The solutions to solve the problems faced by partners are: Providing Appropriate Technology in processing products made from coconut and nuts; Providing knowledge about good processing methods (GMP), sanitation and processing hygiene (SSOP) storage and packaging, marketing, and business management; and provide assistance with processing equipment and business capital. The output targets that have been achieved are applied technology for processing coconut and nuts; The activity has been published in several online mass media, the turnover of the two partners has increased; Product quality and quantity increased.